2022
DOI: 10.1111/joim.13528
|View full text |Cite
|
Sign up to set email alerts
|

BMI is positively associated with accelerated epigenetic aging in twin pairs discordant for body mass index

Abstract: Background Obesity is a heritable complex phenotype that can increase the risk of age‐related outcomes. Biological age can be estimated from DNA methylation (DNAm) using various “epigenetic clocks.” Previous work suggests individuals with elevated weight also display accelerated aging, but results vary by epigenetic clock and population. Here, we utilize the new epigenetic clock GrimAge, which closely correlates with mortality. Objectives We aimed to assess the cross‐sectional association of body mass index (B… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 59 publications
5
15
0
Order By: Relevance
“…The results derived from the replication of the individual-level analyses in a large Finnish cohort study were apparently similar to those derived from the primary analyses, providing additional evidence that also high blood pressure is associated with accelerated aging. These findings are in line with previous research related to the association between MetS and epigenetic aging [ 8 , 9 , 15 , 17 19 , 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…The results derived from the replication of the individual-level analyses in a large Finnish cohort study were apparently similar to those derived from the primary analyses, providing additional evidence that also high blood pressure is associated with accelerated aging. These findings are in line with previous research related to the association between MetS and epigenetic aging [ 8 , 9 , 15 , 17 19 , 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the fifth step, a class of participants with high BMI was extracted. Previous studies have shown the role of being overweight or obese in biological aging ( Lundgren et al, 2022 ). After including the sixth class, the information criteria still showed considerable improvement, but the AvePPs for several classes were below 0.8.…”
Section: Resultsmentioning
confidence: 99%
“…A connection exists between Body Mass Index (BMI) and aging. Lundgren et al ( 53 ) found that higher BMIs correlate positively with accelerated epigenetic aging. Santos et al ( 54 ) discussed the molecular mechanisms connecting obesity with aging, emphasizing the similarities in metabolic dysfunction and the potential for obesity to speed up aging.…”
Section: Discussionmentioning
confidence: 99%